Menakar Distorsi Radikalisme Agama Terhadap Teori dan Praksis Beragama - Romelus Blegur (Litbang STFT Widya Sasana Malang, 2023)
This research focus on related to the issue of religious radicalism as a phenomenon that unsettles relations among adherents of different religions. Its influence is so large and widespread that it has an impact on distortions among religious adherents, both in theory and in practice. Nonetheless, this problem can actually be overcome if adherents of religions with all their uniqueness are willing to live side by side in religious maturity which is fostered through mutual respect and enrichment through their religious values. The method used in this research is literature research by referring to literary sources in the form of books and journal articles that are relevant to the research topic. The result of this research is that, radicalism with all its tendencies to distort religious ways can be measured through maintaining and cultivating discussion space, educating maturity of tolerance, and building a shared ethical culture. These efforts cannot only be limited to academics at the contextual level, but must also exist in the wider community through the praxis level as a form of confirmation of the values that have been conceptualized